2016
DOI: 10.1111/ped.12747
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selective head cooling versus whole‐body cooling

Abstract: There were no significant differences in adverse effects, 12 month neuromotor development, or mortality rate between SHC and WBC in newborns with HIE, born after >35 weeks of gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…A research study comparing selective head cooling therapy with whole body cooling therapy in newborns with hypoxic ischemic encephalopathy uncovered no difference between the two methods in terms of adverse effects and short-term results (Atici et al, 2015). Other research studies have also reached similar conclusion about hypoxic ischemic encephalopathy (Sarkar et al, 2009a,b; Celik et al, 2016). However, it was reported that local hypothermia is better than general hypothermia with a significantly lower rate of severe cortex lesions (Rutherford et al, 2005).…”
Section: Hypothermia Induction Methodssupporting
confidence: 71%
“…A research study comparing selective head cooling therapy with whole body cooling therapy in newborns with hypoxic ischemic encephalopathy uncovered no difference between the two methods in terms of adverse effects and short-term results (Atici et al, 2015). Other research studies have also reached similar conclusion about hypoxic ischemic encephalopathy (Sarkar et al, 2009a,b; Celik et al, 2016). However, it was reported that local hypothermia is better than general hypothermia with a significantly lower rate of severe cortex lesions (Rutherford et al, 2005).…”
Section: Hypothermia Induction Methodssupporting
confidence: 71%
“…Two methods of cooling have been used in clinical trialsselective head cooling and whole body cooling. One small single-centre trial compared both methods of cooling and found no difference in outcomes at 12 months of age in infants enrolled (29). Larger clinical trials found similar effects on death and disability outcomes when either method was compared with placebo (30).…”
Section: Which Methods Should Be Used To Provide Hypothermia?mentioning
confidence: 99%
“…The same team of researchers conducted a small randomized study (17 in SHC vs. 12 in WBC group) and recorded the death rate at 41 vs. 33% and survivors without disability of 18 vs. 33% in the SHC and WBC respectively [32]. However, the differences did not reach the level of statistical significance, which may be ascribed to a limited study group.…”
Section: Discussionmentioning
confidence: 99%